Retrospective study of absorbable gelatin sponge soaked in triamicinolone acetonide as interpositioning material in temporomandibular joint ankylosis in 350 patients - U.S. Pal; Nimisha Singh; Laxman R. Malkunje; R.K. Singh; Satish Dhasmana; Arvind Kumar Yadav; Sharad Chand (Journal of Oral Biology and Craniofacial Research)
Aim: To evaluate the feasibility and usefulness of absorbable gelatin sponge soaked in triamcinolone acetonide as an interposition material in the treatment of temporomandibular joint (TMJ) ankylosis. Materials and methods: This retrospective study was conducted in 350 patients of TMJ ankylosis who visited our outpatient department between 2000 and 2010, and were treated by the same surgeon. Patients were randomly divided into two groups, where in group 1, absorbable gelatin sponge soaked with triamcinolone acetonide was interposed in the surgical gap created after arthroplasty and in group 2, temporalis fascia was interposed. Preoperative assessment included history and physical examination, along with cause of ankylosis, Postoperative observation were undertaken for maximum mouth opening (MMO), facial nerve paralysis and recurrence. Results: At one year follow-up, in group 1 MMO ranged from 35 to 45 mm with no case of re-ankylosis while in the other group 25–43 mm, with re-ankylosis in 20 patients (13.69%). Conclusion: The findings of this study showed successful management of TMJ ankylosis using absorbable gelatin sponge soaked in triamcinolone acetonide in cases which did not require condylar reconstruction.